Photocatalysis - Bignozzi, Carlo Alberto; Alexander, B.D. (Bruce D.) (Topics in current chemistry, 2011)
Metal Oxide Photoanodes for Water Splitting, by J. Augustynski, B.D. Alexander and R. Solarska; Hydrogen Production with Nanostructured and Sensitized Metal Oxides, by Stefano Caramori, Vito Cristino, Laura Meda, Roberto Argazzi and Carlo Alberto Bignozzi; Surface Nanostructures in Photocatalysts for Visible-Light-Driven Water Splitting, by Kazuhiko Maeda and Kazunari Domen; Artificial Photosynthesis Challenges: Water Oxidation at Nanostructured Interfaces, by Mauro Carraro, Andrea Sartorel, Francesca Maria Toma, Fausto Puntoriero, Franco Scandola, Sebastiano Campagna, Maurizio Prato and Marcella Bonchio; Photocatalytic Reduction of CO2: From Molecules to Semiconductors, by Tatsuto Yui, Yusuke Tamaki, Keita Sekizawa and Osamu Ishitani; Design of Heterogeneous Photocatalysts Based on Metal Oxides to Control the Selectivity of Chemical Reactions, by Andrea Maldotti and Alessandra Molinari.